Occurrence of Central Nervous System Complications of Respiratory Syncytial Virus Infections: A Systematic Review with Meta-Analysis - Matteo Riccò; Antonio Cascio; Silvia Corrado; Marco Bottazzoli; Federico Marchesi; Renata Gili; Pasquale Gianluca Giuri; Davide Gori; Paolo Manzoni (MDPI AG, 2024)
An increasing base of evidence suggests that respiratory syncytial virus (RSV) infections may be associated with neurological complications. In accord with the PRISMA statement, we performed a systematic review and meta-analysis on the occurrence of encephalitis and encephalopathy associated with documented RSV infections. PubMed, Embase, and Scopus databases were searched for eligible observational studies published up to 10 April 2024. Raw data included the occurrence of RSV infections among cases of encephalitis and/or encephalopathy and cases of encephalitis and/or encephalopathy among series of RSV infections. Data were pooled in a random effects model. Case reports were also collected, and their data pooled as a cumulative series. Heterogeneity was assessed using the I2 measure, while reporting bias was assessed by means of funnel plots and regression analysis. A total of 15 studies for a total of 7719 RSV infections and 1631 cases of encephalitis were analyzed. Moreover, 27 case reports and case series were retrieved, for a total of 84 individual cases of encephalitis/encephalopathy occurring during a documented RSV infection. A pooled prevalence of 2.20 cases of encephalitis/encephalopathy per 100 RSV cases (I2 = 99%) was calculated, while a prevalence of RSV infections among cases of encephalitis/encephalopathy was estimated to 3.53 per 100 cases for studies on respiratory specimens (I2 = 48%) and 0.37 per cases on central nervous system (CNS) specimens (I2 = 0%). Detection of RSV within the CNS was relatively rare (17.86% of pooled case reports), being associated with male gender (adjusted odds ratio [aOR] 5.021, 95% confidence interval [95%CI] 1.104 to 22.831) and recovery with long-term sequelae (aOR 5.699, 95%CI 1.152; 28.183). Case fatality ratio was estimated to be 0.43 per 100 cases on observational studies and 10.71% in case reports, a difference likely due to publication bias. In summary, RSV represented a not frequent but notable cause of encephalitis/encephalopathy in adults and children. The paucity of available studies not only recommends a cautious appraisal of our results but stresses the clinical significance of future studies on incident cases of encephalitis and/or encephalopathy.